THE ROLE OF THE RURAL AGRIBUSINESS FINANCING PROGRAM IN INCREASING THE INCOME OF FARMER GROUP MEMBERS IN PAGAR MANIK - Ni'mal Hamdi; Dian Dhika; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to analyze the effect of the rural agribusiness financing program on the business development and income of farmer group members in Pagar Manik Village, Silinda District. The research method used was a survey with a quantitative descriptive approach to 22 respondents. Data were collected through interviews and questionnaires, then analyzed using frequency distribution and comparison before and after the program. The results showed that the majority of respondents were women (81.82%) and were in the productive age group of 35–44 years (40.91%). The educational level of respondents was dominated by elementary school graduates (36.36%). The types of businesses run were quite diverse with a dominance in the farming sector (27.27%) and trade (22.73%). The financing program was proven to increase the average business capital from Rp2,500,000 to Rp6,500,000. In addition, respondents' income also increased from an average of Rp1,200,000 to Rp1,850,000 per month. Most respondents (45.45%) stated that the program had an impact on increasing the types of businesses.